Electroporation of CRISPR/Cas9 Targeting Neurogenin 3 (NGN3) in Porcine Embryos and Its Effects on Mosaicism and Off-Target Effects by Next Generation Sequencing (NGS) - Insung Park; Sergio Navarro-Serna; Raquel M. Pinho; Trish Berger; Elizabeth A. Maga; Joaquín Gadea; Seung K. Kim; Pablo J. Ross (Re:GEN Open)
Abstract Introduction: CRISPR/Cas9-mediated editing of embryos through microinjection is limited in efficiency because of high rates of mosaicism and off-target mutations. Electroporation has been proposed as an easier and faster procedure compared to single embryo injection. Methods: Using a synthetic guide-RNA targeting porcine NGN3, we optimized the electroporation conditions to effectively introduce CRISPR/Cas9 in porcine zygotes and evaluate its effects on mosaicism and off-targets. Results: A numerical increase in the mutation rates was observed as embryos were electroporated with increasing concentrations of gRNA (5 ng/μl, 10 ng/μl, and 25 ng/μl) and Cas9 protein (10 ng/μl, 20 ng/μl, and 50 ng/μl) (1:2ratio) without compromising embryo development. Mosaicism results assessed by long-read targeted sequencing of embryos revealed that electroporation with the highest concentration of CRISPR/Cas9 resulted in 57.14% mosaic embryos, accompanied by a significant reduction in the average allele variants (2.43 alleles per embryo) compared to the lowest concentration (4.56 alleles per embryo). Off-target results suggested that no unintended indels were observed when electroporation with the highest CRISPR/Cas9 concentration (25 ng/μl:50 ng/μl) was used. Conclusion: Embryo electroporation with 25 ng/μl:50 ng/μl of CRISPR/Cas9 targeting porcine NGN3 resulted in a very high mutation efficiency, minimal mosaicism, and no off-target mutations.